3(x+1)+1+2x+2x=2(2x+2)+x

1st distribute the 3 into the paraentheses 3(x) and 3(1) and

at the same time distribute the 2 into the (2x+2) to get 2(2x) and 2(2) rewrite the equation

**3x +3**+1 +2x +2x =

**4x +4**+x, the

**bold**lettering is the "new" stuff

2nd: combine like terms on each side but not together(remember like terms have the same variable so x terms with x terms and no x numbers with no x numbers)

3x +

*3 +1*+2x +2x =**4x**+4 +**1x ---->**7x +*4*=**5x**+4 The underline terms were combined, the italics terms were combined and the bold terms combined.Now let's take a look at this equation. 7x +4 = 5x +4. Is there any number that you can multiply by 5 or 7 and add 4 and get the same number? yes and let's find it.

since there is a 4 on each side of the equals sign we will subtract 4 from each side.

7x +4

**- 4**= 5x +4**- 4**-----> 7x +0 = 5x + 0 ----> 7x = 5xnow think about this again. Is there a number that we can multiply by 7 and by 5 and get the same results?

Let's keep going.

7x = 5x, subtract 5x from both sides. 7x

**- 5x**= 5x**- 5x**------> 2x = 02 times what number is 0? or algebraically: 2x = 0, divide each side by 2. 2x

**/2**= 0**/2**--->*x = 0*Please notice how whenever I reduced the equation I performed an operation(plus, minus, mult., divide) to
BOTH sides identically.

recheck:

3(0+1) +1 +2(0) +2(0) = 2(2(0) +2) + 0 ----> 3(1) +1 +0 = 2(0+2) + 0 ---> 3 + 1 = 2(2)--->4=4, true!